Hydroxyl transfer versus cyclization reaction in the gas phase: Sequential loss of NH3 and CH2CO from protonated phenylalanine derivatives - Zheng, Mingyu; Zhang, Xiaoping; Cheng, Yihao; Sun, Lili; Zhang, Xinglei (Frontiers in Chemistry, 2023)
Collisional activation of protonated phenylalanine derivatives deamination products leads to hydroxyl skeletal rearrangement versus cyclization reaction, and to form hydroxylbenzyl cation via elimination of CH2CO. To better clarify this unusual fragmentation reaction, accurate mass measurements experiments, native isotope experiments, multiple-stage mass spectrometry experiments, different substituents experiments and density functional theory (DFT) calculations were carried out to investigate the dissociation mechanistic pathways of protonated phenylalanine derivatives deamination products. In route 1, a three-membered ring opening reaction and a 1,3-hydroxyl transfer (from the carbonyl carbon atom to interposition carbon atom of carbonyl) occurs to form 3-hydroxy-1-oxo-3-phenylpropan-1-ylium, followed by dissociation to lose CH2CO to give hydroxy(phenyl)methylium. In route 2, a successive cyclization rearrangement reaction and proton transfer occurs to form 2-hydroxylphenylpropionyl cation or protonated 2-hydroxy-4H-benzopyran, followed by dissociation to lose CH2CO or CH≡COH to give 2-hydroxylbenzyl cation. In route 3, a successive hydroxyl transfer (from the carbonyl carbon atom to the ortho carbon atom on benzene) and two stepwise proton transfer (1,2-proton transfer to the ipso-carbon atom of the phenyl ring followed by 1,3-proton transfer to the ortho carbon atom of carbonyl) occurs to form 2-hydroxylphenylpropionyl cation, which subsequently dissociates to form 2-hydroxylbenzyl cation by elimination of CH2CO. DFT calculations suggested that route 1 was more favorable than route 2 and route 3 from both a kinetic and thermodynamic point of view.